Asymmetric Total Synthesis of Hasubanan Alkaloids: Periglaucines A–C, N, O‐Dimethyloxostephine and Oxostephabenine. Issue 2 (2nd December 2022) - Ding, Shaolei; Shi, Yingbo; Yang, Baochao; Hou, Min; He, Haibing; Gao, Shuanhu
Abstract: We report herein the asymmetric total synthesis of periglaucines A–C, N, O ‐dimethyloxostephine and oxostephabenine. The key strategies used include: 1) a Rh I ‐catalyzed regio‐ and diastereoselective Hayashi‐Miyaura reaction to connect two necessary fragments; 2) an intramolecular photoenolization/Diels–Alder (PEDA) reaction to construct the highly functionalized tricyclic core skeleton bearing a quaternary center; 3) a bio‐inspired intramolecular Michael addition and transannular acetalization to generate the aza[4.4.3]propellane and the tetrahydrofuran ring. Abstract : Asymmetric total synthesis of the hasubanan alkaloids periglaucines A–C, N, O ‐dimethyloxostephine and oxostephabenine is described. The key strategies include: 1) a Rh I ‐catalyzed regio‐ and diastereoselective Hayashi‐Miyaura reaction; 2) an intramolecular photoenolization/Diels–Alder (PEDA) reaction; and 3) bio‐inspired intramolecular Michael addition and transannular acetalization.